Ole-Oxy, a Semi-Synthetic Analog of Oleuropein, Ameliorates Acute Skin and Colon Inflammation in Mice - Nikolaos V. Angelis; Efthymios Paronis; Georgia Sarikaki; Antonios Kyriakopoulos; Anna Agapaki; Pigi-Maria Niotopoulou; Christina C. Knai; Pavlos Alexakos; Odyssefs Liagkas; Konstantinos F. Mavreas; Constantin N. Baxevanis; Alexios-Leandros Skaltsounis; et al. (MDPI AG, 2024)
Inflammation is a key process in the pathophysiology of various diseases, with macrophages playing a central role in the inflammatory response. This study investigates the anti-inflammatory potential of a newly synthesized analog of oleuropein (OP), the major olive tree (Olea europaea) metabolite. This derivative of OP, named Ole-Oxy, was designed by introducing an oxygen atom between the aromatic ring and the aliphatic chain of OP, to enhance interaction with proteins and improve bioactivity. Ole-Oxy demonstrated notable anti-inflammatory effects in vitro, particularly in phorbol 12-myristate 13-acetate-differentiated THP-1 macrophages, where it markedly reduced interleukin-6, tumor necrosis factor-α, and reactive oxygen species (ROS) levels, surpassing the effects of OP. In vivo, Ole-Oxy was evaluated in mouse models of acute skin and colon inflammation, showing significant efficacy in C57BL/6J mice, likely due to their Th1-biased immune response. Our results suggest that Ole-Oxy modulates inflammation through ROS scavenging and differential macrophage activation, underscoring the need for further research to fully elucidate its mechanism of action and optimize its pharmacokinetic properties for future therapeutic applications.